The Role of Islamic Philosophy in the Formation of a Nation’s Cultural Identity - Nisa, Yuanita Nurul; Apriliyana, Apriliyana; Lotfi, Fatima Zahra; Zainal, Zainal; Apriana, Dewi (Al Irsyad: Jurnal Studi Islam, 2025)
Philosophy plays a crucial role in shaping a nation's cultural identity by understanding cultural roots, worldview, morality, and cultural concepts in response to the continuously evolving challenges of globalization. This study aims to analyze the role of Islamic philosophy in shaping cultural identity through ethical, moral, and spiritual values that influence social and cultural life. This research employs a literature review method to examine relevant scholarly works, assess current knowledge, and identify research gaps as a foundation for further study. The results indicate that Islamic philosophy plays a crucial role in shaping Indonesia’s cultural identity by integrating Islamic values with local culture, as well as education and political policies that support moderation and inclusivity. This approach strengthens social harmony within a pluralistic society. Islamic philosophy not only enriches the intellectual tradition but also serves as a foundation for fostering tolerance and understanding among different groups. These findings emphasize the importance of combining cultural and religious aspects in developing policies and education that can inclusively and sustainably strengthen the national cultural identity. Conclusion: Philosophy shapes a nation's cultural identity through values and critical reflection, although literature-based studies remain limited.